2016
DOI: 10.18045/zbefri.2016.1.119
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Capital Structure: An Empirical Study of Companies From Selected Post-Transition Economies

Abstract: The goal of this paper is to examine if there are any determinants that systematically influence the capital structure of the companies in the Balkan

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
39
0
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 51 publications
6
39
0
5
Order By: Relevance
“…Therefore, successful change management is the key to any organization that wants to survive and succeed in today's highly competitive environment. Organizations are dealing with various kinds of changes, for example changes in market conditions, workforce demographics and diversity, technological innovations, an increased focus on customer and quality, shortage of talent and economical changes (Noe, 2002;Božić & Rajh, 2016;Arsov & Naumoski, 2016;Misankova, 2016;Rajnoha & Dobrovič, 2011). When managing these changes, organizations face obstacles regarding their smooth implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, successful change management is the key to any organization that wants to survive and succeed in today's highly competitive environment. Organizations are dealing with various kinds of changes, for example changes in market conditions, workforce demographics and diversity, technological innovations, an increased focus on customer and quality, shortage of talent and economical changes (Noe, 2002;Božić & Rajh, 2016;Arsov & Naumoski, 2016;Misankova, 2016;Rajnoha & Dobrovič, 2011). When managing these changes, organizations face obstacles regarding their smooth implementation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a more complex view of the model, firms with more investments maintain low-risk debt capacity and issue less debt (Fama & French, 2002). Some studies indicated that leverage increases with growth opportunities (Booth et al, 2001;Arsov & Naumoski, 2016;Burucu & Öndeş, 2016;Erol, Aytekin and Abdioğlu, 2016). However, Titman & Wessel (1988), Karadeniz et al (2009), Cortez & Susanto (2012), Liang et al (2014), and Cevheroglu-Acar (2018) show an insignificant relation between leverage and growth opportunities.…”
Section: Growth Opportunitiesmentioning
confidence: 99%
“…According to this theory, firms tend to issue shares instead of debt when prices are high, and tend to repurchase equity when prices are low. Baker and Wurgler (2002) find evidence that leverage increases (decreases) when the market value is low (high). Corporate leverage is negatively related to the historical market valuations.…”
Section: Introductionmentioning
confidence: 96%
“…(2001) provided empirical evidence that capital structure theory is not portable across borders due to different institutional structures and other country-specific factors. Črnigoj & Mramor (2009) provide a detailed insight with respect to capital structure of Slovenian firms, as do Arsov & Naumoski (2016) for Macedonian firms, and Hernadi & Ormos (2012) for Central and Eastern European SMEs. Research proves that similar factors influence capital choice in developed and emerging markets (Booth, Aivazian, and Demirguc-Kunt 2001).…”
Section: Literature Reviewmentioning
confidence: 99%